2013
DOI: 10.1016/j.etp.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant lymphoproliferative disorder associated with immunosuppressive therapy for renal transplantation in rhesus macaques (Macaca mulatta)

Abstract: Human post-transplant lymphoproliferative disorder (PTLD) is an abnormal lymphoid proliferation that arises in 1–12% of transplant recipients as a consequence of prolonged immunosuppression and Epstein–Barr viral infection (EBV). Nonhuman primates, primarily rhesus macaques (Macaca mulatta), have been used extensively in research models of solid organ transplantation, as the nonhuman primate immune system closely resembles that of the human. Lymphocryptovirus of rhesus monkeys has been characterized and shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The development of NHP models of organ transplantation concurrently provided NHP models for EBV-associated post-transplant lymphoproliferative disorder (PTLD). A fraction of old-world NHPs that were treated with immunosuppressive drugs and received allogeneic grafts were found to develop LPDs that harbored their inherent LCVs [28,37,38]. Schmidtko and others reported that among 160 consecutive renal transplant recipients of cynomolgus monkeys (Macaca fascicularis), 5.6% developed lymphoproliferative lesions similar to human PTLD in incidence, morphology, and immunophenotype [37].…”
Section: Lpd/lymphoma Induced By Lcvs Inherent To Nhps In Immunocomprmentioning
confidence: 99%
“…The development of NHP models of organ transplantation concurrently provided NHP models for EBV-associated post-transplant lymphoproliferative disorder (PTLD). A fraction of old-world NHPs that were treated with immunosuppressive drugs and received allogeneic grafts were found to develop LPDs that harbored their inherent LCVs [28,37,38]. Schmidtko and others reported that among 160 consecutive renal transplant recipients of cynomolgus monkeys (Macaca fascicularis), 5.6% developed lymphoproliferative lesions similar to human PTLD in incidence, morphology, and immunophenotype [37].…”
Section: Lpd/lymphoma Induced By Lcvs Inherent To Nhps In Immunocomprmentioning
confidence: 99%
“…Coinfections with rhesus LCV (Macacine herpesvirus 4) and SIV in macaques have been associated with malignant B cell lymphomas and oral lesions resembling hairy leukoplakia (Feichtinger et al, 1992;Baskin et al, 1995). A posttransplantation lymphoproliferative disorder has been described in cynomolgus macaques following renal transplantation and has a predilection for extranodal involvement (Schmidtko et al, 2002;Page et al, 2013).…”
Section: Epstein-barr Virus (Ebv) That Infect Both New and Oldmentioning
confidence: 99%
“…Such is an example is provided in an NHP renal transplantation study using T cell depletion combined with costimulatory blockade. All eight recipients in this study had viral infections, and three of eight developed posttransplant lymphoproliferative disorder (46). Considering the potential effects on the protective memory T cell pool is critical when improving the efficacy of lymphoablation in transplant recipients.…”
Section: Improving the Efficacy Of Lymphoablation: Risks And Benefitsmentioning
confidence: 93%
“…To reduce the risk of opportunistic infections, prophylactic therapies are often used to counterbalance the negative effects of lymphoablation (45). All eight recipients in this study had viral infections, and three of eight developed posttransplant lymphoproliferative disorder (46). Such is an example is provided in an NHP renal transplantation study using T cell depletion combined with costimulatory blockade.…”
Section: Improving the Efficacy Of Lymphoablation: Risks And Benefitsmentioning
confidence: 98%